Computationally efficient brushless permanent magnet motor modelling - Welford, J.; Apsley, J.; Forsyth, A.; Sophian, Ali (IET, 2014)
Physically derived mathematical models of motors are frequently used to simulate system performance. These can be constructed at various levels of fidelity depending on the application requirements. To accurately capture the dynamics of brushless permanent magnet motors, the effects of electrical commutation should be included. Short time-step simulations are required to include electrical effects explicitly. If the experimental time durations are large, for example during thermal analysis, this type of model can take unacceptably long to run. This work develops a new motor model that includes commutation effects implicitly, and is therefore capable of operating using increased time-steps, significantly reducing simulation time. The effects of winding resistance and inductance within the model ensure that it produces similar results to a fully commutated 3-phase model. The new model is demonstrated through comparison against other models and real motor test results. This validation process is performed in the frequency domain.